Copper Chaperone for Superoxide Dismutase Promotes Breast Cancer Cell Proliferation and Migration via ROS-Mediated MAPK/ERK Signaling - Li, Yanping; Liang, Ronghui; Zhang, Xiaoya; Wang, Jiyan; Shan, Changliang; Liu, Shuangping; Li, Leilei; Zhang, Shuai (Frontiers in Pharmacology, 2019)
Copper chaperone for superoxide dismutase (CCS) is a critical component of oxidation-reduction system and functions as a potential tumor promoter in several cancers. However, the function and clinical significance of CCS in breast cancer remains unclear. Here, we found CCS was highly expressed in breast cancer, where it promoted breast cancer cell proliferation and migration. Suppression of CCS expression was sufficient to attenuate the phosphorylation level of ERK1/2, and increase the accumulation of reactive oxygen species (ROS). Mechanistically, we found that knockdown of CCS decreases the activity of ERK1/2 mediated by the accumulation of ROS, which leads to the inhibition of cell proliferation and migration. In summary, these results indicated that CCS promotes the growth and migration of breast cancer cells via regulating the ERK1/2 activity mediated by ROS.